(untitled) (Journal of Applied Oral Science, 2013)
The relationship between orthodontic force and friction produced from an archwire and brackets affects the sliding of the wire in the leveling stage. Objective: The purpose of this study was to evaluate the relationship between force and friction in a small esthetic nickel-titanium (Ni-Ti) wire. Material and Methods: Five esthetic wires (three coated and two plated) and two small, plain Ni-Ti wires (0.012 and 0.014 inches) were used. We performed a three-point bending test according to ISO 15841 and the drawing test with a dental arch model designed with upper linguoversion of the lateral incisor in the arch (displacements of 0.5, 1.0, 2.0 and 3.0 mm), and evaluated the relationship between them. Results: Unloading bending forces of all wires at displacements of less than 1.0 mm were larger than friction forces, but all friction forces at displacements exceeding 2.0 mm were larger than unloading bending forces. The arch likely expands when displacement from the proximal brackets exceeds 1.0 mm. The friction force of a martensite 0.014-inch Ni-Ti wire was significantly greater than those of the other esthetic and austenitic wires. Conclusions: A wire with the smallest possible friction force should be used in cases with more than 1.0 mm displacement.